ANALISIS GEOMETRIK JALAN DENGAN CIVIL 3D DAN SIG PADA UNIVERSITAS NUSA CENDANA - Frans, John H.; Sir, Tri M. W.; Wanggur, Klaudius (Jurnal Teknik Sipil, 2020)
Jalan merupakan sarana penunjang kegiatan akademik dalam kawasan kampus UNDANA. pertumbuhan jumlah mahasiswa meningkat tiap tahunnya yang berdampak pada volume kendaraan terus bertambah. Analisis geometrik bermanfaat dalam memberikan lebar jalur jalan ideal sesuai dengan kriteria perencanaan geometrik jalan. Selisih elevasi pengukuran menggunakan total station dan menggunakan GPS adalah sebesar -2,283 m. Analisa kapasitas jalan nilai derajat kejenuhan dari segmen 1 sebesar 1.339, segmen 2 0.571, segmen 3 0,311, segmen 4 0.252. Analisa geometrik jalan segmen yang memenuhi standar perencanaan hanya pada segmen 2 dengan lebar jalan 7 m. Analisis alinyemen horisontal pada sebelas tikungan yang ada perlu adanya pelebaran perkerasan di tikungan. Tikungan PI 1 membutuhkan pelebaran perkerasan sebesar 1,390 m, tikungan PI 2 2,286 m, tikungan PI 2,270 m, tikungan PI 4 3,495 m, tikungan PI 5 3,495 m, tikungan PI 6 membutuhkan pelebaran perkerasan sebesar 3,000 m, tikungan PI 7 membuthkan pelebaran perkerasan 2,875, tikungan PI 8 2,838 m, tikungan PI 9 2,382 m, tikungan PI 10 2,920 m, tikungan PI 11 1,795 m. Dari ketiga cara analisis geometrik diberikan rekomendasi peningkatan geometrik jalan pada kawasan kampus UNDANA. Lebar jalan 7 m, lebar lajur 3,5 m, lebar trotoar 2,5 m.Road is a means of supporting academic activities within the UNDANA campus area. the growth in the number of students increases every year which impacts on the volume of vehicles continues to grow. Geometric analysis is useful in providing the width of the ideal road path according to the geometric planning criteria of the road. Measurement elevation difference using total station and using GPS is -2,283 m. Road capacity analysis the degree of saturation value of segment 1 is 1,339, segment 2 is 0.571, segment 3 is 0.311, segment 4 is 0.252. Segment road geometric analysis that meets the planning standard is only in segment 2 with a road width of 7 m. Horizontal alignment analysis of the eleven bends required widening of the pavement around the corner. Bend PI 1 requires pavement widening of 1,390 m, bend PI 2 2,286 m, bend PI 2,270 m, bend PI 4 3,495 m, bend PI 5 3,495 m, bend PI 6 requires widening of pavement by 3,000 m, bend PI 7 requires widening of pavement 2,875 , PI 8 curve 2,838 m, bend PI 9 2,382 m, bend PI 10 2,920 m, bend PI 11 1,795 m. Of the three methods of geometric analysis, recommendations were given for increasing the geometric path of the UNDANA campus area. The width of the road is 7 m, the width of the lane is 3.5 m, the width of the sidewalk is 2.5 m.